Analisis Perilaku dan Faktor Penyebab Perilaku Penggunaan Antibiotik Tanpa Resep di Surabaya - Dewi Paskalia Andi Djawaria; Adji Prayitno Setiadi; Eko Setiawan (Media Kesehatan Masyarakat Indonesia, 2018)
There is limited information regarding the behavior and determinant factors of non-prescribed use of antibioticsinSurabaya. The purpose of this study was to identify the behavior and the most influential factors in usingantibiotics without prescription. This was a cross sectional studyconducted insubjects who bought antibiotics withoutprescription in 90 pharmacies in Surabaya during December 2014-April 2015. Eight complex questions wereused to identify the behavior. The contributing factors of non-prescription behavior were identified by using twostatistical methods, including: descriptive analysis by comparing the mean of the questions in each factor theme,and factor analysis using orthogonal rotation (varimax). There were 267 respondents involved in this study. Themajority of respondents who bought antibiotics without prescription ranged from age 21-30 years old (36.33%),frequency buying antibiotics 1/month (45.70%), intended for themselves (56.55%), buying antibiotics soon afterthe symptoms appeared (33.70%), and intended for runny nose/flu indication (21.30%). Based on the descriptivestatistic, the theme “aspects that encourage” was found as the factor contributed to the use of antibiotics withoutprescription. The value of cumulative percent total variance found in the factor analysis method explained was48.03%, with the biggest value on the first factor that was 23.91%. The most influential factor was the ease of accessto get the antibiotics and the saving of money. The results of this study can be used to determine the appropriateintervention to deal with the use of antibiotics without prescription in the pharmacies.Considering the complexcauses of such behavior, pharmacist should not be blamed as the only cause of non-prescribed use of antibiotics.